Conversor eletrônico de alto fator de potência para alimentação de leds aplicando a técnica input current shaper - Pereira, Guilherme Gindri (2017)
This work presents analysis, simulation, design and implementation of an integrated topology consisting of two static DC-DC converters to supply power LEDs, presenting high power factor. Power factor correction is essential when supplying LEDs in order to comply with regulations such as the NBR 16026. A discontinuous conduction mode operated Flyback converter is used to implement the power factor correction stage, applying the input current shaper technique. This technique consists on the connection of a converter operating as a resistance emulator placed between the main rectifier and the DC bus, in order to increase the conduction angle of the rectifier diodes, obtaining low current harmonics injected to the mains. Low current harmonics are necessary in order to comply with IEC 61000-3-2 Class C regulations for lighting equipment. The use of a Flyback converter operating as a resistance emulator provides reduced power processing, which increases the overall efficiency of the converter. Power control stage is performed by a Buck converter, also in discontinuous conduction mode, due to its simplicity and step-down voltage characteristic. Both converters are integrated, thus reducing the number of active switches and related auxiliary control circuitry, presenting reduced component count, volume and total cost. Furthermore, two-stage configuration allows for bus capacitance reduction, owing to the effect of low frequency filtering provided by the second stage. In this way, electrolytic capacitors can be avoided or capacitor volume can be reduced, thus increasing the reliability of the LED driver, which is an essential feature pursued in this type of converters. Therefore, in addition to a high power factor and reduced total harmonic distortion, it is expected for this driver to present high efficiency and no electrolytic capacitors, thus obtaining long lifetime. The driver also presents dimming capability. A prototype has been implemented and the experimental results obtained are presented at the end of this paper in order to validate the proposed technique.